2015
DOI: 10.1371/journal.pone.0136786
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Evidence of Compensatory Brain Mechanisms in Early-Stage Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic central nervous system disorder characterized by white matter inflammation, demyelination and neurodegeneration. Although cognitive dysfunction is a common manifestation, it may go unnoticed in recently-diagnosed patients. Prior studies suggest MS patients develop compensatory mechanisms potentially involving enhanced performance monitoring. Here we assessed the performance monitoring system in early-stage MS patients using the error-related negativity (ERN), an event-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
(48 reference statements)
3
15
0
Order By: Relevance
“…With regard to our ERP findings, we found group differences with MS patients showing less N2 differentiation between CR and hit trials than HC. Our findings are consistent with the existing literature demonstrating associations between aberrant ERP brain activity and cognitive impairments in MS [55][56][57] . The finding of group differences in N2 adaptation to increasing taskload is strikingly similar to our prior MoBI work comparing younger and older adults 28 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With regard to our ERP findings, we found group differences with MS patients showing less N2 differentiation between CR and hit trials than HC. Our findings are consistent with the existing literature demonstrating associations between aberrant ERP brain activity and cognitive impairments in MS [55][56][57] . The finding of group differences in N2 adaptation to increasing taskload is strikingly similar to our prior MoBI work comparing younger and older adults 28 .…”
Section: Discussionsupporting
confidence: 93%
“…However, further tests of the N2/d-prime association in MS are required to support the aforementioned conclusion. Of note, recent ERP investigations in MS assessing cognition while participants were stationary (i.e., cognitive-only task) reported evidence in support of compensatory neural functions [55][56][57] . For example, Lopez-Gongora found larger ERP amplitudes in MS relative to HC, even though groups did not differ in their response inhibition performance.…”
Section: Msmentioning
confidence: 99%
“…Theories on compensatory mechanisms with healthy aging assume that significant neural remodeling occurs, while at the behavioral level performance remains relatively unimpaired (Festini et al, 2018). This mechanism has also been described in early stages of neurodegenerative diseases in which task performance is still comparable to agematched healthy controls (Trujillo et al, 2014;Gerrits et al, 2015;Audoin et al, 2003;Lopez-Gongora et al, 2015). Indeed, in a recent study, working memory CT showed similar task-related activity decrease in healthy adults and a population of early-stage cognitively healthy MS patients (Aguirre et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies also show that shorter and longer RRMS disease duration with similar disabilities are characterized by distinct patterns of FC, involving predominantly sensory and cognitive networks, respectively [40]. Besides, increased FC between brain regions implies the use of brain reserves to ameliorate cognitive impairment in early-stage MS patients (disease duration < 5 years), which is generally interpreted as a compensatory mechanism [34,41]. During the course of disease after reaching a maximal level, brain FC enhancement decreases and decreased FC participates in disability progression, according to a longitudinal resting-state fMRI study [42].…”
Section: Comparison Between Patients In the Remitting Phase Of Rrms Amentioning
confidence: 99%